Sanctions and Legal Compliance in Marriage Registration: A Comparative Implementation of Islamic Family Law in Indonesia and Malaysia - Fitra, Tasnim Rahman; Yusof, Noratinah Binti; M. Radiamoda, Anwar (Tuah Foundation, 2025)
Unregistered marriages remain challenging in implementing Islamic family law in Indonesia and Malaysia. This article aims to comparatively analyze sanction systems and legal compliance levels in marriage registration in Indonesia and Malaysia based on Islamic family law perspectives, identify factors influencing the effectiveness of legal sanctions, and integrate the maqāṣid al-sharī'ah approach with legal compliance theory to provide a new theoretical framework for understanding marriage registration. Using a juridical-normative approach with comparative methodology, this article analyzes Law Number 16 of 2019 in Indonesia and Act 303 Islamic Family Law (Federal Territories) 1984 in Malaysia. The article concludes that there is a correlation between sanction amounts and public compliance levels, where stricter sanctions in Malaysia (fines of RM1,000 and imprisonment of up to six months) prove more effective than nominal sanctions in Indonesia (Rp7,500). Significant differences are also identified in law enforcement mechanisms and the accessibility of marriage registration systems. The maqāṣid al-sharī'ah approach to marriage registration, which emphasizes the protection of fundamental values in Islam, proves capable of bridging the gap between traditional Islamic law and modern administrative needs. This article implies the importance of reformulating marriage registration policies in Indonesia, including restructuring sanctions and strengthening technology-based registration systems.